Pemberian Aromaterapi Lavender terhadap Peningkatan Kualitas Tidur pada Lansia (Journal of Telenursing (JOTING), 2025)
This study aims to determine the effect of lavender aromatherapy on improving sleep quality in older people. The research method used is a pre-experimental design case study with a one-group pre-test - post-test design. The results of the study showed that based on the results of the statistical test, namely the Paired sample t-test, a p-value of 0.004 was obtained, so the P-Value